Navy Tactical Applications Guide. Volume 3. North Atlantic and Mediterranean Weather Analysis and Forecast Applications. Meteorological Satellite Systems. - Fett, Robert W; Bohan, Walter A (1981)
Case studies describing regional environmental analysis and forecast applications based on satellite data and conventional meteorological observations for the North Atlantic and Mediterranean areas are presented. Topics include blocking, cyclogenesis, coastal zone phenomena, and ocean- atmosphere interaction. The studies provide insights into identifiable patterns of weather development that occur frequently, so that once the basic pattern is recognized at an early stage this information can be used for improved weather analysis and forecasting. The volume also contains a user oriented section on current operational meteorological satellite systems that describes imagery acquisition and distribution, sensor systems, and spectral characteristics. In addition, sample imagery is included for each of the meteorological satellite systems. (Author) See also AD-A135 466, AD-B024 969 and AD-A150 097.